Tuberculosis is associated with expansion of a motile, permissive and immunomodulatory CD16(+) monocyte population via the IL-10/STAT3 axis - Lastrucci, Claire (2015)
The human CD14+ monocyte compartment is composed by two subsets based on CD16 expression. We previously reported that this compartment is perturbed in tuberculosis (TB) patients, as reflected by the expansion of CD16+ monocytes along with disease severity. Whether this unbalance is beneficial or detrimental to host defense remains to be elucidated. Here in the context of active TB, we demonstrate that human monocytes are predisposed to differentiate towards an anti-inflammatory (M2-like) macrophage activation program characterized by theCD16+CD163+MerTK+pSTAT3+ phenotype and functional properties such as enhanced protease-dependent motility, pathogen permissivity and immunomodulation. This process is dependent on STAT3 activation, and loss-of-function experiments point towards a detrimental role in host defense against TB. Importantly, we provide a critical correlation between the abundance of the CD16+CD163+MerTK+pSTAT3+ cells and the progression of the disease either at the local level in a non-human primate tuberculous granuloma context, or at the systemic level through the detection of the soluble form of CD163 in human sera. Collectively, this study argues for the pathogenic role of the CD16+CD163+MerTK+pSTAT3+ monocyte-to-macrophage differentiation program and its potential as a target for TB therapy,and promotes the detection of circulating CD163 as a potential biomarker for disease progression and monitoringof treatment efficacy.